Use of metabolites, metabolithotropic agents and nutritional supplements in sports and sports medicine: a modern view on the problem - Bielenichev, I. F.; Gorchakova, N. A.; Doroshenko, E. Yu.; Samura, I. B.; Ryzhenko, V. P.; Bukhtiiarova, N. V. (Modern medical technology, 2023)
Aim. The purpose of this study was to conduct an up-to-date semantic analysis of the results of our own research and literature data on the medical and pharmacological characteristics of metabolites, metabolitotropic agents and nutritional supplements, the peculiarities of their use in sports practice and sports medicine. Materials and methods. This study used bibliosemantic, analytical, logical, and generalization methods. The life sciences and biomedical information bibliographic databases MEDLINE, EMBASE, Medline (PubMed), Web of Science, and Cochrane Central were searched to find publications in English that matched the research keywords. The authors carried out an independent search and selection of articles, assessment of the quality of the data, compliance of the presentation and interpretation with the main idea of the study, with the formation of the final list of references. Results. Based on the analysis of modern literature data and the results of our own studies, a generalized medical and pharmacological characteristic of metabolite agents, metabolitotropic drugs and nutritional supplements that can influence the main and compensatory mechanisms of macroergic phosphates production under the influence of physical activity is presented. The mechanisms of action, indications for use and main side effects of drugs and food additives based on ATP, malate, succinate, citrate, pyruvate, carnitine, carnosine, etc. are presented. Conclusions. Semantic analysis data indicate that an urgent problem for sports medicine physicians and pharmacologists is the development and use of metabolites, metabolitotropic agents and nutritional supplements, as well as approaches to their rational combination to improve energy metabolism, replenish ATP reserves in the body that will help ensure the intensity muscular activity and simultaneously protect target organs.